2021
DOI: 10.1097/grf.0000000000000641
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Techniques in Pregnancy and Postpartum

Abstract: Maternal stress can perturb physiology and psychiatric health leading to adverse outcomes. This review investigates the effectiveness of several mindbody therapies-namely biofeedback, progressive muscle relaxation, guided imagery, tai chi, and yogaas interventions in reducing maternal stress and other pregnancy-related conditions. Through randomized trials, these techniques have shown promising benefits for reducing pain, high blood pressure, stress, anxiety, depressive symptoms, labor pain and outcomes, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Labor is a physiological process a mother undergoes to deliver an infant, which is accompanied by pain and pressure[ 15 ]. Providing scientific and reasonable care management for primiparas is therefore of great value to improve their birthing experience and delivery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Labor is a physiological process a mother undergoes to deliver an infant, which is accompanied by pain and pressure[ 15 ]. Providing scientific and reasonable care management for primiparas is therefore of great value to improve their birthing experience and delivery outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for noninvasive therapies that target stressors implicated in this study is tremendous. Randomized trials have shown that mind-body techniques and other nonpharmaceutical interventions including tai chi, guided imagery, progressive muscle relaxation, and yoga, have reduced mood symptoms during pregnancy ( 58 ). Noninvasive techniques such as massage during pregnancy and postpartum have also been valuable in improving mood, decreasing perception of pain during labor ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of practicing relaxation techniques in reducing anxiety was also found in a recent study during the lockdown [ 33 ]. Furthermore, a recent review of clinical studies discovered that there was a preventive effect of practicing relaxation techniques on postpartum mood disturbances [ 34 ]. The potential benefits of relaxation techniques and enhanced outdoor activity on maternal mental health and promoting these activities in new mothers during the lockdown period should be advocated.…”
Section: Discussionmentioning
confidence: 99%